Does one size fit all?: a meta-analysis examining the predictive ability of the Level of Service Inventory (LSI) with Aboriginal offenders - Wilson, Holly A. (Criminal justice and behavior, 2014)
The application of common risk assessment measures, such as the Level of Service Inventories (LSI), to Aboriginal offenders has been a criticized practice. The belief that Aboriginal offenders have distinct needs has informed the argument that existing risk-need assessments cannot adequately capture their risk. To explore this, the present meta-analysis reviewed 16 samples to test the extent to which LSI scores predict recidivism for Aboriginal compared with non-Aboriginal offenders. In addition, one large sample was used to examine the similarities in recidivism rates per LSI score for Aboriginal and non-Aboriginal offenders. Results indicated that the LSI predicts recidivism for Aboriginal offenders; however, for five of eight subscales, it predicts with less accuracy compared with non-Aboriginal offenders. In addition, the LSI underclassifies low-scoring Aboriginal offenders, but accurately estimates recidivism rates for higher scoring offenders. Implications for research into culturally-specific risk factors and the application of current risk factors to Aboriginal offenders are explored.